Reforming the Rules on the Division of Joint Property: A Progressive Legal Approach - Khairina Khairina; Khairani Khairani; Roni Efendi; Kasmuri Kasmuri; Okky Afrianto (JURIS (Jurnal Ilmiah Syariah), 2024)
According to Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Law (KHI) Articles 96 and 97 on the division of joint property, each person in a marriage that dissolves due to divorce or death is entitled to half of the property that is joint property. However, the legal circumstances presented in Payakumbuh Religious Court's Decision No. 657/Pdt.G/2022/PA Pyk did not follow the KHI and gave the plaintiff (the husband) a portion of ¼ and the defendant (the wife) a share of ¾ of the joint property. Therefore, the goal of the analysis presented in this article is to respond to the judge's ratio decidendi when it comes to joint property that are unrelated to the KHI. Then, a more thorough explanation of progressive law as a method of legal change in the realm of community property is provided. The research approach employed in this paper is the normative legal method. The investigation's findings demonstrate that the judge's reasoning is predicated on the idea that the wife's inherited assets, rather than the husband's income from their marriage, constitute the joint property at issue in the proceedings. In terms of income, living expenses, or child-education expenses, the plaintiff was unable to demonstrate how much he contributed to the defendant's household during their time together. The plaintiff could not provide sufficient evidence to support his claim that he could afford to buy the property, house, and four-wheeled vehicle that are at issue. According to the judge's ruling, progressive law satisfies societal legal requirements. The judge's ruling about the contribution of joint assets served as a legal justification for not dividing joint assets in half, based on the facts of the case